S87 Are oral steroids effective in treating the symptoms of acute lower respiratory tract infection in non-asthmatic adults? The Oral Steroids for Acute Cough (OSAC) placebo-controlled randomised trial. (12th November 2015) - Hay, AD; Downing, HE; Brookes, ST; Young, G; Harnden, A; Hollinghurst, SP; Kendrick, D; Little, P; May, MT; Moore, MV; Orton, E; Wang, K; et al.
Abstract : Background: The majority of UK adults experience at least one lower respiratory tract infection (LRTI, or acute bronchitis) a year. Despite an absence of evidence in this patient group, some GPs prescribe inhaled or oral corticosteroids. OSAC sought to demonstrate 'proof of concept' symptomatic effectiveness of a moderate dose of oral corticosteroid for adults without asthma or COPD with acute LRTI. Methods: OSAC was a double blind, placebo controlled RCT set in GP practices in England, powered to investigate if oral prednisolone reduces the duration of moderately bad or worse cough and/or the severity of its associated symptoms, when compared to placebo, by at least 20%. Adults (≥18 years) with acute (≤28 days) cough, for whom same-day antibiotics were not clinically indicated, and without asthma or COPD, received 40 mg oral prednisolone or matched placebo for 5 days. Symptom diaries, completed for up to 28 days, measured two primary outcomes: the duration of moderately bad or worse cough; and the average severity of all symptoms on days 2 to 4 on a scale of 0–6. We sought to demonstrate a minimum clinically important reduction of 20% in each outcome. Results: 398 participants were randomised to either prednisolone or placebo tablets (198 and 200 respectively) from 54 UK primary care sites. Attrition was lower than expected, giving over 85% power for the two primary outcomes. Data were analysed on an intention-to-treat basis. The median duration of moderately bad or worse cough was 5 days in both groups (IQRs 2–8 and 3–8 for prednisolone and placebo respectively). Adjusting for trial centre and baseline characteristics, this gave a hazard ratio of 1.11 (95% CI 0.89 to 1.39, p = 0.35). Symptom severity was lower in the prednisolone group (mean 1.99 vs 2.16), adjusted difference -0.090 (-0.212 to 0.003, p = 0.152). Conclusions: We found no evidence that a moderately high dose of oral corticosteroid reduced either duration of moderately bad (or worse) cough, or symptom severity at days 2 to 4 in adults without asthma or COPD with LRTI not requiring immediate antibiotic treatment. Lower dose oral or high dose inhaled corticosteroids are also unlikely to be beneficial.